Early venous filling is associated with unfavorable outcomes in acute ischemic stroke with large vessel occlusion after mechanical thrombectomy: a real-world analysis - Jiaxin Han; Yixuan Wu; Zihan Wang; Jianfeng Han; Guogang Luo; Kang Huo (BMC Neurology)
Abstract Background The presence of early venous filling (EVF) post-mechanical thrombectomy (MT) in acute ischemic stroke (AIS) patients has been observed, yet its prognostic value for clinical outcomes remains underexplored. This study aimed to assess the correlation between EVF and poor clinical outcomes in AIS patients who underwent MT. Materials and methods This retrospective analysis included AIS patients with large vessel occlusions treated with MT at the First Affiliated Hospital of Xi’an Jiaotong University from January 2018 to June 2023. The primary outcome was mRS at 90 days, secondary outcomes included hemorrhagic transformation, symptomatic intracranial hemorrhage, and malignant brain edema. The study used inverse probability weighting for balancing baseline characteristics and employed univariate and multivariate logistic regression analyses to explore the association between EVF and clinical outcomes. G*Power was used to calculate the sample size. Results Among 307 patients, 75 (24.4%) presented with EVF. Patients with EVF had significantly higher rates of unfavorable outcomes at 90 days (76.00% vs. 46.12%, P < 0.001). Multivariate analysis revealed significant associations between EVF and unfavorable outcome (odds ratio [OR] = 2.69, 95%CI [1.37–5.26], P = 0.004), hemorrhagic transformation (OR = 3.11, 95%CI [1.73–5.62], P < 0.001), symptomatic intracranial hemorrhage (OR = 3.24, 95%CI 1.42 to 7.37, P = 0.005), and malignant brain edema (OR = 3.06, 95%CI [1.56–6.01], P = 0.001). Stratified analysis showed EVF group with a baseline Alberta Stroke Program Early CT (ASPECT) score of ≤ 8 exhibited a higher risk of unfavorable outcomes compared with patients in the non-EVF group (OR = 2.64, 95%CI [1.03–6.73], P = 0.042). Mediation analysis indicated that malignant brain edema accounted for 35.42% of the correlation between EVF and unfavorable outcomes. Conclusions This study establishes EVF as an independent risk factor for unfavorable outcomes after MT in AIS. Therefore, EVF in conjunction with a low ASPECT score provides essential insights for identifying patients at high risk for unfavorable outcomes.